2018
DOI: 10.7762/cnr.2018.7.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Diet Modification Based on the Enhanced Recovery After Surgery Program (ERAS) in Patients Undergoing Laparoscopic Colorectal Resection

Abstract: The enhanced recovery after surgery (ERAS) program aims to maximize the recovery of patients by minimizing pre- and postoperative complications and stress. The program recommends providing preoperative carbohydrate (CHO) supplements and starting an early postoperative diet to reduce the fasting duration. Based on these recommendations, we implemented preoperative CHO supplementation and initiated an early postoperative diet in patients undergoing laparoscopic colorectal resection. We observed 3 patients as fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Studies conducted in different countries indicate that the earlier oral feeding starts for the patients the shorter the time of the first defecation and the duration of hospital stay is [21,22], not the presence of anastomosis leakage and abscess and the patient satisfaction was high [23]. In laparoscopic colorectal resection surgery, in addition to preoperative oral carbohydrate administration in accordance with ERAs recommendations, patients, who switched to post-operative oral nutrition early had faster recovery of their postoperative clinical functions, decrease in recovery time and decrease in-hospital stay [24]. In this study, none of the patients have been begun the liquid food on the 2nd hour and solid food intake on the 4th hour of the post-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in different countries indicate that the earlier oral feeding starts for the patients the shorter the time of the first defecation and the duration of hospital stay is [21,22], not the presence of anastomosis leakage and abscess and the patient satisfaction was high [23]. In laparoscopic colorectal resection surgery, in addition to preoperative oral carbohydrate administration in accordance with ERAs recommendations, patients, who switched to post-operative oral nutrition early had faster recovery of their postoperative clinical functions, decrease in recovery time and decrease in-hospital stay [24]. In this study, none of the patients have been begun the liquid food on the 2nd hour and solid food intake on the 4th hour of the post-operative period.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical protocols should therefore be revised. 23 In a case study, 24 three patients were followed before and after laparoscopic colorectal resection: one with control fasting, another with shortened preoperative fasting and the third with shortened pre and postoperative fasting. Even with the shortened protocol, the latter two patients underwent preoperative fasting for approximately 17 hours, while the control patient remained in a fasting state for 43 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The medical literature shows but a few reports of similar protocols applied in leading cancer hospitals specialized in treating patients with more advanced stages of cancer who are, in the great majority, malnourished [9][10][11][20][21][22] .…”
Section: Jejum Pré-operatório Abreviado Favorece Realimentação Pós-opmentioning
confidence: 99%
“…Besides, randomized clinical studies comparing ERAS to traditional postoperative care showed a reduction in the length of hospital stay for the ERAS group [8][9][10][11][12][13][14] . Similarly, in 2005, project ACERTO (Aceleração da Recuperação Total -Total Recovery Acceleration) was started in Brazil, based on the concepts of the ERAS group 4,6 .…”
mentioning
confidence: 99%